(untitled) (Al-IRTIQA: Journal of Arabic Education and Linguistics, 2026)
This study aims to examine the effectiveness of using Quizizz as a learning medium in improving students’ learning outcomes in nahwu (Arabic grammar) within balaghah instruction. The study employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The subjects of this study were students at Institut Agama Islam Negeri Kerinci, who were divided into an experimental group and a control group. Data were collected through learning outcome tests in the form of pretest and posttest, while data analysis was conducted using an independent sample t-test to determine the differences in learning outcomes between the two groups. The results of the study indicate that there is a significant improvement in the learning outcomes of students who were taught using Quizizz compared to those who were taught using conventional methods. In addition, the use of Quizizz also enhances students’ motivation, engagement, and active participation in the learning process. Therefore, it can be concluded that Quizizz is an effective alternative learning medium for improving students’ learning outcomes in nahwu within balaghah instruction.